2015
DOI: 10.1038/mp.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of the amygdala and ventral striatum predict stress-related problem drinking in young adults: possible differential markers of affective and impulsive pathways of risk for alcohol use disorder

Abstract: Prior work suggests there may be two distinct pathways of alcohol use disorder (AUD) risk: one associated with positive emotion enhancement and behavioral impulsivity, and one associated with negative emotion relief and coping. We sought to map these two pathways onto individual differences in neural reward and threat processing assessed using BOLD fMRI in a sample of 759 undergraduate students (426 women, mean age 19.65±1.24) participating in the Duke Neurogenetics Study. We demonstrate that problem drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 65 publications
7
87
0
Order By: Relevance
“…Based upon our previous findings in alcohol and opiate dependence for the [ 11 C]Ro15‐4513 PET analysis, we selected right hippocampus and NAc as a priori ROIs, and we chose two additional a priori ROIs based upon their established role in impulse control: OFC and amygdala (Goldstein and Volkow 2002; Jentsch and Taylor 1999; Ko et al 2015; Nikolova et al 2016). As previous work (Clark et al 2012; Michalczuk et al 2011) has shown that NU, as a mood‐related subgroup of impulsivity, is most strongly associated with GD, we chose to test for correlations between UPPS‐P NU and a priori selected brain regions.…”
Section: Methodsmentioning
confidence: 99%
“…Based upon our previous findings in alcohol and opiate dependence for the [ 11 C]Ro15‐4513 PET analysis, we selected right hippocampus and NAc as a priori ROIs, and we chose two additional a priori ROIs based upon their established role in impulse control: OFC and amygdala (Goldstein and Volkow 2002; Jentsch and Taylor 1999; Ko et al 2015; Nikolova et al 2016). As previous work (Clark et al 2012; Michalczuk et al 2011) has shown that NU, as a mood‐related subgroup of impulsivity, is most strongly associated with GD, we chose to test for correlations between UPPS‐P NU and a priori selected brain regions.…”
Section: Methodsmentioning
confidence: 99%
“…In 759 emerging adults (average age 19.6 ± 1.2 years), 2 distinct markers of stress-related problem drinking were identified. 15 One group exhibited elevated threat-induced activations of the amygdala coupled with reduced reward-related activations of the ventral striatum. The second group exhibited the converse pattern: elevated reward-related activations in the ventral striatum and diminished threat-induced activations in the amygdala.…”
Section: J Psychiatry Neurosci 2017;42(4)mentioning
confidence: 97%
“…1 Threat-related reactivity of the amygdala, for example, is strongly associated with negatively reinforced problem drinking. 10 Connectivity between the amygdala and the hippocampus is associated with maladaptive emotional processing, 11 and alterations in hippocampal network activation and connectivity have been shown to predict relapse. 12 The prefrontal cortex has extensive connections with subcortical structures that regulate emotional processing, including the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…We sought to determine the effects of naltrexone at standard dose (50 mg) during negative emotional processing between groups dependent on alcohol alone, dependent on alcohol and drugs (both in abstinence) and healthy control volunteers. On the basis of previous research showing altered activation in limbic and cortical networks during negative emotional processing in substance-dependent individuals, 1,[10][11][12][13][14][15] including the processing of evocative 16 and negative emotional images, 38,39 we hypothesized that the dependent groups would show increased activation in the amygdala, the mPFC and the hippocampus in response to aversive images. In light of preclinical evidence, 29 we further hypothesized that these effects would be modulated by naltrexone depending on the degree of childhood adversity experienced.…”
Section: Introductionmentioning
confidence: 99%